Menelusuri Tradisi Horja Patibal Sere sebagai Warisan Budaya Suku Mandailing di Panyabungan, Mandailing Natal - Sepriani, Laila; Rohani, Laila (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2025)
This study aims to examine the Horja Patibal Sere tradition among the Mandailing ethnic group in Panyabungan, Mandailing Natal Regency. Employing a qualitative research method, the study utilized in-depth data collection through observation, interviews, documentation, and data analysis techniques. The findings reveal that Patibal Sere is a compulsory customary ritual held at night, involving family members, religious figures, and traditional leaders. During the ceremony, the agreed-upon mahar (bridal dowry) is presented on a ceremonial tray along with symbolic items such as burangir (betel leaves), yellow rice, areca nut, banana leaf tips, and a traditional long cloth. Following the symbolic handover, the bride’s mother carries the dowry, representing a gesture of nurturing, protecting, and caring for the continuity of the marriage. The Mandailing people, an ethnic group from North Sumatra, possess a rich and distinctive cultural heritage. The Patibal Sere tradition, passed down for generations, remains an essential component of the customary marriage rites. It reflects the deep-rooted values, identity, and social cohesion within the Mandailing community, particularly emphasizing the sacredness and communal nature of marriage through ancestral rituals.‎